Chemical and Sensory Characterisation of Two Rubus rosifolius (Red Raspberry) Varieties - Theresa F. Rambaran; Camille S. Bowen-Forbes (International Journal of Food Science)
Raspberries are economically important fruits, being highly valued for their taste and medicinal properties. Prior to our recent finding, the occurrence of different varieties of Rubus rosifolius growing in Jamaica had not been previously reported. Upon close observation of the plants, differences in various physical features pointed to the existence of two distinct plant morphotypes, which were described as Red “R” and Wine Red “WR.” With an aim to determine which variety may be more favourable for value-added food production, we undertook their physicochemical and sensory analysis. This characterisation led to the rationalisation of the differences in the perceived sensory properties of these biologically active fruits. Total phenolic content was determined using the Folin-Ciocalteu reagent assay, and the identification and quantification of anthocyanins were done via HPLC-MS and HPLC-UV, respectively. Proximate and physicochemical analyses were also carried out. The findings of the analyses were associated with those of a consumer sensory analysis. The WR fruits had a greater quantity of the deep red anthocyanin, cyanidin-3-glucoside (66.2 mg/100 g FW), and a significantly lower lightness value. They also received a significantly higher sweetness score, which is associated with their higher total sugar content (4.8 g/100 g) and maturity index (6.7). The R fruits had a higher quantity of the orange-coloured pelargonidin-3-rutinoside (17.2 mg/100 g FW) and significantly higher titratable acidity (1.3 g citric acid/100 mL), the latter being associated with its significantly more sour taste. The high total phenolic contents suggest a health-functional value of these R. rosifolius berry fruits. Our findings, which revealed that the WR variety was the preferred choice among consumers, may be used to guide future product-development endeavours of these commercially valuable fruits.